Penggunaan E-Money Berdasarkan Undang-Undang Nomor 7 Tahun 2011 Tentang Mata Uang - Situngkir, Roman (Universitas Muhammadiyah Sumatera Utara, 2018)
The recent use of e-money raises the pros and cons after the policy of liability for the use of e-money for payments at toll booths. There is an opinion that the liability for the use of e-money violates and contradicts Act No. 7 of 2011 about Currency. So it is interesting to see how the real existence of e-money based on Act No. 7 of 2011 about Currency. In this paper, it is concluded that the use of e-money is not contradictory to Act No. 7 of 2011 about Currency. Because e-money is only recognized as tool or payment system and dose not replace the official currency of rupiah. But then the obligation to use only e-money in toll booths and not to receive payment in cash would be another matter. Not giving the choice to the community to choose between cash or non-cash payment using e-money actually causes discrimination and injustice in society. Should the government give people the choice to choose between cash payments or using e-money.